Kebersyukuran dan Kesejahteraan Subjektif Guru Honor: Sebuah Pendekatan Kuantitatif di Pakel - Sriwahyuni, Nasi’ Desti; Faruq, Faruq; Sari, Citra Ayu Kumala Sari (IDEA: Jurnal Psikologi, 2025)
Subjective well-being is a critical aspect that influences the quality of life and performance of teachers, particularly honorary teachers who face financial challenges and limited career opportunities. One key factor that can enhance subjective well-being is gratitude, a positive emotion that fosters appreciation for life and the blessings received. This study aims to analyze the influence of gratitude on the subjective well-being of honorary teachers in Pakel District. A quantitative approach was employed, involving 147 teachers as the sample, selected using purposive sampling techniques. The research instruments included a gratitude scale and a subjective well-being scale, both measured using a Likert scale. Data were analyzed using simple linear regression. The results indicate that gratitude has a positive and significant influence on subjective well-being (R²=52.1%; p<0.05). This finding suggests that higher levels of gratitude correspond to better subjective well-being among teachers. However, 47.9% of the variation in subjective well-being is influenced by other factors, such as social support, working conditions, and demographic characteristics. This study highlights the importance of fostering gratitude as a strategy to improve the subjective well-being of teachers, particularly honorary teachers.